HUBUNGAN PENGETAHUAN PEKERJA SEKS KOMERSIAL TENTANG HIV/AIDS DENGAN KEPATUHAN MENGGUNAKAN KONDOM DI LOKALISASI TELUK BAKAU KOTA BATAM TAHUN 2018 - Hesti, Hesti; Aryaneta, Yenni (Universitas Batam, 2018)
HIV (Human Immunodeficiency Virus) is a virus causes AIDS attacking human white cells which is the most important part of the human immune system. The purpose of this study was to determine the relationship between knowledge of Commercial Sex Workers about HIV / AIDS with obedience using Condoms. This study adopted a cross sectional design with 49 samples of commercial sex workers taken by purposive sampling: there was a significant relationship between knowledge of commercial sex workers about HIV / AIDS and condom use behavior in the prostitution area of Teluk Bakau Batam in 2018. Based on the findings, to increase condom use 100% in the prostitution area, there is a need for policies from the local government as a policy maker concerning 100% of condom use in each area, as well as increasing health education activities in order to prevent HIV / AIDS transmission.Â